2010
DOI: 10.1074/jbc.m110.159921
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel WDR5-binding Site That Recruits RbBP5 through a Conserved Motif to Enhance Methylation of Histone H3 Lysine 4 by Mixed Lineage Leukemia Protein-1*

Abstract: Histone modification is well established as a fundamental mechanism driving the regulation of transcription, replication, and DNA repair through the control of chromatin structure. Likewise, it is apparent that incorrect targeting of histone modifications contributes to misregulated gene expression and hence to developmental disorders and diseases of genomic instability such as cancer. The KMT2 family of SET domain methyltransferases, typified by mixed lineage leukemia protein-1 (MLL1), is responsible for hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
118
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(123 citation statements)
references
References 52 publications
5
118
0
Order By: Relevance
“…Several biochemical and structural studies have shown that the ␤-propeller-like structure of WDR5 has an arginine binding pocket that can associate with N-terminal residues of histone H3 and MLL by its WDR5 interaction motif (7,11,(13)(14)(15)(16)(17)(18)(19). Unlike WDR5, the C terminus of RBBP5, a region outside of the WD40 domains, is important for protein-protein interactions and can interact with ASH2L and WDR5 (7,20). Other studies have also shown that RBBP5, together with WDR5, ASH2L, and DPY30, significantly facilitates MLL1 methyltransferase activity on histone H3K4, suggesting that RBBP5 forms a stable complex with WDR5, ASH2L, and DPY30 (21,22).…”
mentioning
confidence: 99%
“…Several biochemical and structural studies have shown that the ␤-propeller-like structure of WDR5 has an arginine binding pocket that can associate with N-terminal residues of histone H3 and MLL by its WDR5 interaction motif (7,11,(13)(14)(15)(16)(17)(18)(19). Unlike WDR5, the C terminus of RBBP5, a region outside of the WD40 domains, is important for protein-protein interactions and can interact with ASH2L and WDR5 (7,20). Other studies have also shown that RBBP5, together with WDR5, ASH2L, and DPY30, significantly facilitates MLL1 methyltransferase activity on histone H3K4, suggesting that RBBP5 forms a stable complex with WDR5, ASH2L, and DPY30 (21,22).…”
mentioning
confidence: 99%
“…Within the MLL complexes, WDR5 recognizes both a WIN (WDR5-interacting) motif of MLL proteins and a short motif of RbBP5. These interactions stimulate the methyltransferase activity of MLL proteins (Patel et al 2008b;Odho et al 2010;Avdic et al 2011). The NSL and MLL/COMPASS complexes were proposed to form a larger assembly that would possess both H3K4 methylation and H4 acetylation activities (Dou et al 2005;Li et al 2009).…”
mentioning
confidence: 99%
“…WDR5 is crucial for the structural integrity of the complex and acts as a bridge linking each member of the KMT2 family (Dharmarajan et al 2012;Zhang et al 2012) to the regulatory subunits RbBP5, Ash2L, and DPY-30 (Odho et al 2010;Avdic et al 2011). In RbBP5, a predicted unstructured region binds to Ash2L and WDR5 and is important for the stimulation of MLL1 methyltransferase activity (Cao et al 2010;Avdic et al 2011).…”
mentioning
confidence: 99%